A Companion to the anthropology of death - 4 0 16; Robben, Antonius C. G. M.; 5 (Hoboken, NJ : John Wiley & Sons, 2018)
Prominent scholars present their most recent work about mortuary rituals, grief and mourning, genocide, cyclical processes of life and death, biomedical developments, and the materiality of human corpses in this unique and illuminating book. Interrogating our most common practices surrounding death, the authors ask such questions as: How does the state wrest away control over the dead from bereaved relatives? Why do many mourners refuse to cut their emotional ties to the dead and nurture lasting bonds? Is death a final condition or can human remains acquire agency? The book is a refreshing reassessment of these issues and practices, a source of theoretical inspiration in the study of death.;With contributions written by an international team of experts in their fields, A Companion to the Anthropology of Death is presented in six parts and covers such subjects as: Governing the Dead in Guatemala; After Death Communications (ADCs) in North America; Cryonic Suspension in the Secular Age; Blood and Organ Donation in China; The Fragility of Biomedicine; and more. A Companion to the Anthropology of Death is a comprehensive and accessible volume and an ideal resource for senior undergraduate and graduate students in courses such as Anthropology of Death, Medical Anthropology, Anthropology of Violence, Anthropology of the Body, and Political Anthropology.;Antonius C.G.M. Robben is Professor of Anthropology at Utrecht University, The Netherlands, and past President of The Netherlands Society of Anthropology. --Book Jacket.
Governing the dead in Guatemala : public authority and dead bodies / Finn Stepputat -- Evolving mortuary rituals in contemporary Japan / Yohko Tsuji -- Revealing brands, concealing labor / George Sanders -- Playing with corpses : assembling bodies for the dead in southwest China / Erik Mueggler -- Death and separation in post-conflict Timor-Leste / Judith Bovensiepen -- Migration, death, and conspicuous redistribution in southeastern Nigeria / Daniel Jordan Smith -- After death : event, marrative, feeling / Michael Lambek -- Reflections on the work of recovery I and II / Beth A. Conklin -- The pursuit of sorrow and the ethics of crying / Oliver Allard -- Mourning as mutuality Jason Danely -- A comparative study of Jewish-Israeli and Buddhist-Khmer trauma descendant discontinued bonds with the genocide dead / Carol A. Kidron -- Facing death : on nourning, empathy and finitude / Devin Flaherty and C. Jason Throop -- What is a mass grave? : toward an anthropology of human remains treatment in contemporary contests of mass violence / Isabeth Anstett -- Death on the move : pantheons and reburials in Spanish Civil War exhumations / Francisco Ferrandiz -- Accountability for mass death, acts of rescue and silence in Rwanda / Jennie E. Burnet -- Impassable visions : the Cambodia to come, the detritus in its wake / Hudson McFann and Alexander Laban Hinton -- Experience, empathy, and flexibility : on participant observation in deadly fields / Ivana Macek -- Learning how to die / Robert Desjarlais -- Whirlpools, glitter and ferocious intruders : the palpability of death in Chachi animism / Istvan Praet -- Shamanic rebirth and the paradox of disremembering the dead among Mapuche in Chile / Ana Mariella Bacigalupo -- After death communications (ADCs) : signs from the other world in contemporary North America / Ellen Badone -- Cryonic suspension as eschatological technology in the secular age / Abou Farman -- From here and to death : the archaeology of the human body / Liv Nilsson Stutz -- Death, corporeality and uncertainty in Zimbabwe / Joost Fontein -- Death, power, and silence : Native Nations' ancestral remains at the Carlisle Barracks, Pennsylvania / Jacqueline Fear-Segal -- In the absence of a corpse : rituals for body donors in the Netherlands / Sophie Bolt -- Death as spectacle : plastinated bodies in Germany / Uli Linke -- The body as medicine : blood and organ donation in China / Charlotte Ikels -- Ethical dilemmas in the field : witchcraft and biomedical aetiology in South Africa / Isak Niehaus -- The disappearance of dying and why it matters / Helen Stanton Chapple -- The fragility of biomedicine : death, detachment and moral dilemmas of care in a Kenyan hospital / Ruth J. Prince -- The new normal : mediated death and assisted dying in the United States / Frances Norwood.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on May 24, 2018).
Keywords: 2 -- 0; 6; Social aspects -- Funeral rites and ceremonies;Death -- 20 -- Cross-cultural studies.;Cross-cultural studies; 20; Electronic books.;Cross-cultural studies